Eocene and Miocene extension, meteoric fluid infiltration, and core complex formation in the Great Basin (Raft River Mountains, Utah). Issue 4 (9th April 2015) - Methner, Katharina; Mulch, Andreas; Teyssier, Christian; Wells, Michael L.; Cosca, Michael A.; Gottardi, Raphaël; Gébelin, Aude; Chamberlain, C. Page
Abstract Metamorphic core complexes (MCCs) in the North American Cordillera reflect the effects of lithospheric extension and contribute to crustal adjustments both during and after a protracted subduction history along the Pacific plate margin. While the Miocene‐to‐recent history of most MCCs in the Great Basin, including the Raft River‐Albion‐Grouse Creek MCC, is well documented, early Cenozoic tectonic fabrics are commonly severely overprinted. We present stable isotope, geochronological (40Ar/39Ar), and microstructural data from the Raft River detachment shear zone. Hydrogen isotope ratios of syntectonic white mica (δ2Hms) from mylonitic quartzite within the shear zone are very low (−90‰ to −154‰, Vienna SMOW) and result from multiphase synkinematic interaction with surface‐derived fluids. 40Ar/39Ar geochronology reveals Eocene (re)crystallization of white mica with δ2Hms ≥ −154‰ in quartzite mylonite of the western segment of the detachment system. These δ2Hms values are distinctively lower than in localities farther east (δ2Hms ≥ −125‰), where 40Ar/39Ar geochronological data indicate Miocene (18–15 Ma) extensional shearing and mylonitic fabric formation. These data indicate that very low δ2H surface‐derived fluids penetrated the brittle‐ductile transition as early as the mid‐Eocene during a first phase of exhumation along a detachment rooted to the east. In the eastern part of the core complex, prominent top‐to‐the‐east ductile shearing, mid‐Miocene 40Ar/39Ar ages, and higher δ2H values of recrystallized white mica, indicate Miocene structural and isotopic overprinting of Eocene fabrics.